2005
DOI: 10.5326/0410227
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Carbon Dioxide Laser for the Ablation of Meibomian Gland Adenomas in Dogs

Abstract: Twelve eyelid meibomian gland adenomas in dogs were surgically ablated using the carbon dioxide (CO(2)) laser. The laser site was not sutured. All procedures resulted in complete removal of the adenoma with no recurrences at 6 months. In addition, no dogs developed corneal disease secondary to the procedure, and the cosmetic appearance of the eyelid margins was good at the end of the 6-month study. Based on results of this study, CO(2) laser ablation of canine meibomian gland adenomas is an effective alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…There are a variety of techniques established to address palpebral masses in dogs. These techniques range from complete simple excision, a variety of blepharoplastic procedures, debulking and cryotherapy, and carbon dioxide laser therapy …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a variety of techniques established to address palpebral masses in dogs. These techniques range from complete simple excision, a variety of blepharoplastic procedures, debulking and cryotherapy, and carbon dioxide laser therapy …”
Section: Introductionmentioning
confidence: 99%
“…1,4 These techniques range from complete simple excision, 1,4,5 a variety of blepharoplastic procedures, 1,6-10 debulking and cryotherapy, 1,[4][5][6][11][12][13] and carbon dioxide laser therapy. 1,14 Previous studies have shown that up to one-third the length of the eyelid can be removed in dogs and still allow for primary eyelid closure 1,3,4,6 without the need for more complex blepharoplastic procedures. 1,3,4,6 If tumor size necessitates excision of greater than one-third of the eyelid length, reconstructive techniques are usually recommended.…”
mentioning
confidence: 99%
“…SCC confined to the cornea/limbus and bulbar conjunctiva can frequently be completely surgically excised via keratoconjunctivectomy 16 . Lamellar keratectomy and conjunctivectomy are usually sufficient to remove all macroscopically abnormal tissue 17 . However, macroscopic removal can leave residual and viable microscopic neoplastic cells.…”
Section: Introductionmentioning
confidence: 99%
“…It performs a precise, controllable, hemostatic, and noncontact atraumatic ablation, with reduction in postoperative pain . One of the applications in this area is the laser excision and ablation of neoplasms, but there are also several laser surgical techniques for correcting entropion …”
Section: Introductionmentioning
confidence: 99%
“…21,24 It performs a precise, controllable, hemostatic, and noncontact atraumatic ablation, with reduction in postoperative pain. 19 One of the applications in this area is the laser excision and ablation of neoplasms, 22,25,27,32 but there are also several laser surgical techniques for correcting entropion. 17 This kind of laser has been used in eyelid entropion repair by making 'X' striations in a linear pattern or longitudinal streaks radiating from the eyelid margin.…”
Section: Introductionmentioning
confidence: 99%